USP10 Targeted Self-Deliverable siRNA to Prevent Scarring in the Cornea - Edward F. Boumil; Nileyma Castro; Andrew T. Phillips; Jon E. Chatterton; Sean M. McCauley; Alexey D. Wolfson; Taisia Shmushkovich; Marc Ridilla; Audrey M. Bernstein (Elsevier, 2020)
Ocular scarring after surgery, trauma, or infection leads to vision loss. The transparent cornea is an excellent model system to test anti-scarring therapies. Cholesterol-conjugated fully modified asymmetric small interfering RNAs (siRNAs) (self-deliverable siRNAs [sdRNAs]) are a novel modality for in vivo gene knockdown, transfecting cells and tissues without any additional formulations. Myofibroblasts are a main contributor to scarring and fibrosis. αv integrins play a central role in myofibroblast pathological adhesion, overcontraction, and transforming growth factor β (TGF-β) activation. Previously, we demonstrated that αv integrins are protected from intracellular degradation after wounding by upregulation of the deubiquitinase (DUB) ubiquitin-specific protease 10 (USP10), leading to integrin cell surface accumulation. In this study, we tested whether knockdown of USP10 with a USP10-targeting sdRNA (termed US09) will reduce scarring after wounding a rabbit cornea in vivo. The wounded corneal stroma was treated once with US09 or non-targeting control (NTC) sdRNA. At 6 weeks US09 treatment resulted in faster wound closure, limited scarring, and suppression of fibrotic markers and immune response. Specifically, fibronectin-extra domain A (EDA), collagen III, and a-smooth muscle actin (p < 0.05), CD45+ cell infiltration (p < 0.01), and apoptosis at 24 (p < 0.01) and 48 h (p < 0.05) were reduced post-wounding. Corneal thickness and cell proliferation were restored to unwounded parameters. Targeting the DUB, USP10 is a novel strategy to reduce scarring. This study indicates that ubiquitin-mediated pathways should be considered in the pathogenesis of fibrotic healing.